2022
DOI: 10.1002/ptr.7525
|View full text |Cite
|
Sign up to set email alerts
|

Total flavonoids of Rhizoma drynariae promote angiogenesis and osteogenesis in bone defects

Abstract: Bone defects are difficult to heal, which conveys a heavy burden to patients' lives and their economy. The total flavonoids of Rhizoma drynariae (TFRD) can promote the osteogenesis of distraction osteogenesis. However, the dose effect is not clear, the treatment period is short, and the quality of bone formation is poor. In our study, we observed the long‐term effects and dose effects of TFRD on bone defects, verified the main ingredients of TFRD in combination with network pharmacology for the first time, exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“… 76 Through the PI3K/AKT/HIF1-α/VEGF pathway, the total flavonoids of Rhizoma drynariae can boost HUVEC migration, proliferation, and vascularization to accelerate bone formation. 44 In this study, we found that HUVECs in the APGGP group had significantly higher expression of PI3K/AKT/HIF1-α/VEGF signal pathway-related proteins, which allowed us to investigate the potential mechanism triggered by the scaffolds with HUVECs. We showed that the APGGP group had much higher neovascularization than that in the other groups in the rat epidermis model.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“… 76 Through the PI3K/AKT/HIF1-α/VEGF pathway, the total flavonoids of Rhizoma drynariae can boost HUVEC migration, proliferation, and vascularization to accelerate bone formation. 44 In this study, we found that HUVECs in the APGGP group had significantly higher expression of PI3K/AKT/HIF1-α/VEGF signal pathway-related proteins, which allowed us to investigate the potential mechanism triggered by the scaffolds with HUVECs. We showed that the APGGP group had much higher neovascularization than that in the other groups in the rat epidermis model.…”
Section: Discussionmentioning
confidence: 79%
“…The PI3K/AKT/HIF1-α/VEGF pathway encourages HUVEC vascularization, proliferation, and migration. 44 Western blotting was used to detect related pathway proteins, and the protein expression of p-PI3K, p-AKT, HIF1-α, VEGF, and CD31 in the APGGP group was significantly increased compared with that in the APG and APGG groups ( Figure 7(b) and ( c )).…”
Section: Resultsmentioning
confidence: 99%
“…Yu Dong et al has reported that BMSCs transplant in bone tunnels can promote the proliferation of cartilage‐like cells, formation of the fibrocartilage‐like tissues, and the improvement of maximum load and stiffness 30 . TFRD is commonly used in bone diseases such as fracture, arthritis, etc 17 . It is a Chinese herbal medicine often used in clinical orthopedics.…”
Section: Discussionmentioning
confidence: 99%
“…30 TFRD is commonly used in bone diseases such as fracture, arthritis, etc. 17 bone mineral density for osteoporotic fractures. 18 Li et al also reveal that TFRD can promote the growth and mineralization of bone graft in a dose-dependent way by facilitating blood vessel formation and upregulating the angiogenesis-related factors via the BMP-SMAD pathway.…”
Section: Tfrd Improves Tendon-bone Healing In Mice and Facilitates Th...mentioning
confidence: 99%
See 1 more Smart Citation